The social construction of sexual violence for female politicians - Tri Vena Putri; Bagong Suyanto (Jurnal Sosiologi Dialektika, 2021)
The phenomenon of sexual violence is illustrated as the iceberg phenomenon. Every year the number of cases of sexual violence increases. Among the victims of sexual violence, women are the most common ones. This study aimed to examine how the social construction of sexual violence from the side of women as female politicians. The research method was qualitative. Primary data were obtained through observation and in-depth interviews. The theory employed was the social construction theory by Peter L. Berger and Thomas Luckmann. The results showed that in the externalization process, sexual violence is a reality that still has weaknesses in its handling in Indonesia due to the existence of patriarchal values in society. The objectification process resulted in a debate between the use of the KUHP and the Elimination of Sexual Violence Bill (RUU PKS) as the legal basis for sexual violence. The internalization process is a reinterpretation of sexual violence after externalization and objectivation. This study concludes, in this process, female politicians interpret sexual violence as an act of attacking the sexuality of the victim which damages the physical and psychological aspects.